UPDATED CHECKLIST OF HERPETOFAUNA IN BALINSASAYAO TWIN LAKES NATURAL PARK, NEGROS ORIENTAL: A LONG-TERM ECOLOGICAL RESEARCH SITE IN THE PHILIPPINES - Jean Henri Oracion; Arnold Rabor; Sharmaine Arjona; Victor Amoroso (BIOTROPIA, 2026)
ARTICLE HIGLIGHTSUpdated checklist reveals rich amphibian and reptile diversity.Twenty-two endemic species found occur only in the Philippines.Seven threatened species highlight the area's conservation importance.Species richness is comparable with other long-term research sites.Continued monitoring may reveal more amphibian and reptile species.ABSTRACTThe Balinsasayao Twin Lakes Natural Park (BTLNP) is one the established Long-term Ecological Research Sites (LTER) in the Philippines. LTER sites are valuable for providing underlying causes for changes in the environment, management of natural resources, and conservation of biodiversity. Through this, researchers could quantify simultaneously certain complex ecological interactions. This primary aim of this study is to assess the herpetofauna to update the existing data on herps, and compare its species richness with other LTER sites. Survey was done by using the cruising method in the established 2-hectare plot, and other areas outside of it. A total of three sampling visits with six field days was spent from the sampling visits on. The findings of this study included detecting 29 herpetofauna species, composed of: 11 amphibian and 18 reptile species, 17 of which are endemic and six are resident. This record represents 54.7% of the total number of 53 species listed by Dolino et al., 2004. There are five species described to be threatened, namely: Platymantis negrosensis, Platymantis hazelae, Limnonectes visayanus, Sanguirana acai, Hydrosaurus pustulatus, Tropidonophis negrosensis, and Oligodon modestus. In comparison with the other LTER sites, albeit having a completely different presence of species, the level of species richness at BTLNP is close to Mt. Hamiguitan. This implies that the habitat is similar in conditions, and the demands of each species are well provided. The presence of the lake itself might be the major reason as it can offer a variety of resources for these species. Many egg laying species are also benefit from it as well. Therefore, its worth should not be undervalued. A longer monitoring and a more systematic sampling is recommended to potentially observe more species that may be unique to BTLNP.